Anatomical and Functional Characterization of Central Amygdala Glucagon-Like Peptide 1 Receptor Expressing Neurons - Zeng, Ningxiang; Cutts, Elam J.; Lopez, Christian B.; Kaur, Simran; Duran, Miguel; Virkus, Sonja A.; Hardaway, J. Andrew (Frontiers in Behavioral Neuroscience, 2021)
Glucagon-like peptide 1 receptors (GLP-1Rs) are highly expressed in the brain and are responsible for mediating the acute anorexigenic actions of widely prescribed GLP-1R agonists. Neurobiological efforts to localize the hypophagic effects of GLP-1R agonists in the brain have mainly focused on the hypothalamus and hindbrain. In this study, we performed a deep anatomical and neurophysiological characterization of GLP-1Rs in the central nucleus of the amygdala (CeA). At an mRNA level, we found that Glp1r is diffusely coexpressed in known CeA subpopulations like protein kinase c δ (Prkcd), somatostatin (Sst), or tachykinin2 (Tac2). At a cellular level, we used Glp1r-Cre mice and viral Cre-dependent tracing to map the anatomical positions of GLP-1R cells across the rostral-caudal axis of the CeA and in CeA subdivisions. We found that Glp1rCeA cells are highly enriched in the medial subdivision of the CeA (CeM). Using whole cell patch clamp electrophysiology, we found that Glp1rCeA neurons are characterized by the presence of Ih-like currents and resemble a low threshold bursting neuronal subtype in response to hyperpolarizing and depolarizing current injections. At rest, we observed that nearly half of Glp1rCeA neurons are spontaneously active. Our data are the first to deeply characterize the pattern of Glp1r in the CeA. Future studies leveraging these data will be important to understanding the impact of GLP-1R agonists on feeding and motivation.